Response of human dental pulp capped with MTA and calcium hydroxide powder - Accorinte, M. L. R.; Loguercio, Alessandro D.; Reis, Alessandra; Carneiro, E.; Grande, R. H. M.; Murata, S. S.; Holland, R. (Operative Dentistry, 2008)
Objectives: To compare the response of human dental pulp capped with a mineral trioxide aggregate (MTA) and Ca(OH) 2 powder. Methods and Material: Pulp exposures were performed on the occlusal floor of 40 permanent premolars. The pulp was then capped with either Ca(OH) 2 powder (CH) or MTA and restored with resin composite. After 30 days (groups CH30 and MTA30) and 60 days (groups CH60 and MTA60), the teeth were extracted and processed for HE and categorized in a histological score system. The data were subjected to Kruskal-Wallis and Conover tests (α=0.05). Results: In regard to dentin bridge formation, CH30 showed a tendency towards superior performance compared to MTA30 (p>0.05), although the products showed comparable results at day 60. In the item Inflammation and General State of the Pulp (p>0.05), CH showed a tendency towards presenting a higher inflammatory response. In the item Other Pulpal Findings, MTA and Ca(OH) 2 showed equal and excellent performance after 30 and 60 days (p>0.05). Conclusion: After 30 days, Ca(OH) 2 powder covered with calcium hydroxide cement showed faster hard tissue bridge formation compared to MTA. After 60 days, Ca(OH) 2 powder or MTA materials showed a similar and excellent histological response with the formation of a hard tissue bridge in almost all cases with low inflammatory infiltrate. © Operative Dentistry, 2008.
Keywords: aluminum derivative; biomedical and dental materials; calcium derivative; calcium hydroxide; mineral trioxide aggregate; oxide; protective agent; resin; silicate; adolescent; adult; comparative study; dental surgery; drug combination; drug effect; endodontics; giant cell; human; macrophage; materials testing; methodology; pathology; premolar tooth; pulpitis; time; tooth pain; tooth pulp; tooth pulp disease; Adolescent; Adult; Aluminum Compounds; Bicuspid; Calcium Compounds; Calcium Hydroxide; Composite Resins; Dental Materials; Dental Pulp; Dental Pulp Capping; Dental Pulp Exposure; Dental Restoration, Permanent; Dentin, Secondary; Drug Combinations; Giant Cells; Humans; Macrophages; Materials Testing; Oxides; Protective Agents; Pulpitis; Silicates; Time Factors; Toothache